The life of the Lord Jesus Christ ; v. 2 a complete critical examination of the origin, contents and connection of the Gospels - Lange, John Peter 1802-; Dods, Marcus, 1834-1909 (Grand Rapids, MI Zondervan, 1958)
Includes bibliographical references.
This edition is reproduced complete and unabridged from the 1972 edition published by T. and T. Clark
Keywords: Jesus Christ -- person and offices; Bible N.T. Gospels -- criticism, interpretation, etc